The effects of leptin on human cytotrophoblast invasion are gestational age and dose-dependent - Rumer, Kristen K.; Sehgal, Shilpi; Kramer, Anita; Bogart, Kevin P.; Winn, Virginia D. (Frontiers in Endocrinology, 2024)
Leptin and its receptors are expressed by the human placenta throughout gestation, yet the role of leptin in early human placental development is not well characterized. Leptin is overexpressed in the placentas from preeclamptic (PE) pregnancies. PE can result from the impaired invasion of fetal placental cells, cytotrophoblasts (CTBs), into the maternal decidua. We hypothesized that elevated leptin levels would impair human CTB invasion. The effects of leptin on the invasion of human CTBs were evaluated using HTR-8/SVneo cells, primary CTBs, and placental villous explants. We found that, prior to 8 weeks gestation, leptin promoted CTB invasion in the explant model. After 11 weeks gestation in explants, primary CTBs and in HTR-8/SVneo cells, leptin promoted invasion at moderate but not at high concentrations. These data suggest that the excess placental leptin observed in PE may cause impaired CTB invasion as a second-trimester defect. Further, the expression of leptin receptors was characterized. Leptin receptor expression did not vary over gestation, however, STAT, PI3K and MAPK pathways showed different signaling in response to varied leptin doses.Leptin's differential effect on trophoblast invasion may explain the role of hyperleptinemia in preeclampsia pathogenesis.